ANALISA FINANSIAL PROYEK BANGUNAN GEDUNG (STUDI KASUS: PROYEK GEDUNG INTENSIF RSSA MALANG) - Firda Eka Damayanti, Fauziah S.C.S. Maisarah, Suselo Utoyo (Prokons: Jurnal Teknik Sipil, 2014)
The 4,333 m2-four-floored Intensive Building development project was carried out to accommodate additional facility to the hospital due to the increasing number of patients. Financial analysis is necessary to find out the project cost and to see the operational cost sufficient to meet the building management for 20 years life span according to the building standard. The aims of this analysis are to find out the project cash flow during the life span, financial report, feasibility analysis, and sensitivity analysis. Some data of budgeting, technical drawings, medical equipment procurement cost, hospitalization and out-patient rates were needed. All of them were obtained from interviews and calculations. While Net Present Value (NPV), Internal Rate of Return (IRR), Benefit Cash Ratio (BCR), Pay Back Period (PP), and sensitivity analysis were employed to determine the financial feasibility. The calculations result in financial analysis of NPV = 32,989,940,121 > 0; BCR = 1.34 > 1; IRR = 18.83% > Minimum Attractive Rate of Return (MARR) = 10%; and PP = 7.2 years. The results of the sensitivity analysis show that the most influential factor is occupancy rate, but the project is feasible.Keywords: feasibility, financial analysis, intensive building.